BANK SYARIAH INDONESIA EFFICIENCY ANALYSIS BEFORE AND AFTER THE MERGER: TWO STAGE DATA ENVELOPMENT ANALYSIS - Ida Busnetty; Heru Kurniawan Susilo; Soeharjoto; Acep R Jayaprawira (RADJA PUBLIKA, 2023)
This study aims to look at the factors that influence efficiency and also this study aims to see the principles of Entity Theory on the level of efficiency. This research uses a type of quantitative research through Data Envelopment Analysis (DEA) and tobit. DEA is used to calculate the efficiency score of Islamic Banks while Tobit is used to analyze the factors that influence the efficiency performance of Islamic Banks with the estimation of the MLE (Maximum Likelihood) method. The software used in this analysis are Microsoft Excel, MaxDEA 8 and Eviews. The variables used in this study are divided into two, namely variables for analyzing efficiency with the DEA method and variables for analyzing factors that affect the level of efficiency. The results of this study are that Islamic banks before the merger from 2016 to 2019 had not reached an efficient level. BRIS and BNIS banks in 2020 have reached an efficient level, while BSM banks in 2020 have not reached an efficient level with a score of 0.97. After the merger was carried out, Islamic banks reached an efficient level with a score of 1. This shows that the purpose of the merger to create more efficient Islamic banks was achieved. The factors that affect the level of technical efficiency are GDP and inflation. Where GDP has a significant positive effect on the level of technical efficiency of Islamic banks while inflation has a significant negative effect on the level of technical efficiency of Islamic banks.